Mitoxantrone as a substitute for daunorubicin during induction in newly diagnosed lymphoblastic leukemia and lymphoma. Issue 5 (19th December 2013) - Nickel, Robert S.; Keller, Frank; Bergsagel, John; Cooper, Todd; Daves, Marla; Sabnis, Himalee; Lew, Glen
<x xml:space="preserve">Abstract</x> Background Daunorubicin, a component of the four‐drug induction chemotherapy regimen for de novo pediatric high‐risk acute lymphoblastic leukemia (ALL) and lymphoblastic lymphoma (LLy), was unavailable in 2011 due to a national drug shortage. During this time, our institution substituted mitoxantrone 6.25 mg/m2 for daunorubicin 25 mg/m2 on induction Days 1, 8, 15, and 22. While mitoxantrone has been shown to be effective for relapsed ALL, it has not been studied in de novo pediatric ALL/LLy. Procedure We conducted a retrospective cohort study of newly diagnosed patients with ALL or LLy at our institution 1/2009–4/2013 to compare induction toxicity and response of patients treated with mitoxantrone versus daunorubicin. Results Eleven patients received mitoxantrone, 121 patients received daunorubicin. Induction toxicities including deaths, intensive care unit admissions, fever, bacteremia, and invasive fungal disease were similar for the two groups. Mean number of days hospitalized during induction was also similar (mitoxantrone 9.7 days vs. daunorubicin 11.2 days, P = 0.60). Minimal residual disease prevalence at the end of induction was not significantly different (mitoxantrone 33.3% vs. daunorubicin 23.0%, P = 0.44). The only significant difference between the groups was that a higher proportion of patients who received mitoxantrone had consolidation delayed due to myelosuppression (mitoxantrone 30.0% vs. daunorubicin 6.0%, P = 0.03). Conclusion Induction toxicity and response for new ALL/LLy patients treated with mitoxantrone in place of daunorubicin were similar to the toxicity and response seen with conventional daunorubicin. Mitoxantrone is a reasonable replacement for daunorubicin in times of drug shortage. Pediatr Blood Cancer 2014;61:810–814. © 2013 Wiley Periodicals, Inc.